CONSUMER INTENTIONS TO PURCHASE HEALTHY FOOD: A THEORY OF PLANNED BEHAVIOR CASE STUDY - Siti Nur Alliyah; Effy Yuswita; Dina Novia Priminingtyas (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
Rising public awareness of health has encouraged lifestyle changes aimed at preventing Non‑Communicable Diseases (NCDs), particularly obesity. Dietary adjustments have increased demand for healthy food and catering services such as Dietindo Catering. However, fluctuating sales of one of its flagship meal box products suggest that consumers do not fully recognize the urgency of healthy eating. This study examines the influence of attitude, subjective norms, perceived behavioral control, and health consciousness on purchase intention toward healthy food products, applying the Theory of Planned Behavior (TPB). A quantitative approach was employed using descriptive statistics and Structural Equation Modeling–Partial Least Squares (SEM‑PLS) with 100 respondents. Data were collected through online questionnaires, interviews, and secondary sources. Results show that 60% of respondents had never purchased, with most being young female students. SEM‑PLS analysis revealed that attitude, subjective norms, and perceived behavioral control significantly affected purchase intention, while health consciousness was positive but not significant.